The final blow to the Stability Pact? EMU enlargement and government debt - Philipp Paulus (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2006)
The continued debate on even the softened Stability and Growth Pact (SGP) highlights that the question of public debt in the European Monetary Union (EMU) needs further scrutiny. Both political economy models for emerging market sovereign debt and exchange rate regimes, as well as models on common pool and debt spillover problems in a monetary union point to an upward drift of public debt for countries joining EMU. In turn, this could lead to the expectation that, the more countries join EMU, the more pressure on an already battered SGP will develop. However, such models and first empirical research tend to focus only on the behaviour of governments - that is, the demand side on the market for government debt. Factors determining the supply side of government debt - i.e. capital markets - are most of the time left out of the analysis. This paper tries to fill this gap by analysing empirically the effects of both public debt demand and supply factors on the budget balances in the EMU candidate countries of Central and Eastern Europe (CEE) as well as in EMU and other OECD countries from 1994 to 2005. The results suggest that, although demand factors seem to have played a more important role than supply factors, some evidence for market conditions limiting new debt is found. More interestingly, despite the SGP disappointment, membership of EMU, as well as the time of the convergence to EMU, so far appears to coincide with more positive budget balances. Since most of the SGP literature assumes that EMU will cause a bias for higher debt due to spillover effects between EMU member countries, this could warrant a different theoretical approach to the impact of monetary unions on government debt.
Keywords: F33; G15; H62; H63; 330; monetary union; fiscal stability; government debt; EMU enlargement